A MATHEMATICAL MODEL OF THE EFFECTS OF IRRIGATION AND NITROGEN FOR UPLANDRICE DURING DRY SEASON IN BADEGGI ENVIRONMENT - Gana, Janet; Badeggi, A. Yahaya; Agboluaje, A. Ayo; Yakubu, A. Aisha (FUDMA Journal of Sciences, 2025)
Rice is one of the major stable foods in Nigeria. It is also a source of energy, income and employment opportunity in Nigeria. The demand for rice in Nigeria has exceeded the production, due to ever increasing population and there is hike in the price of rice. The aim of this work is to apply a Mathematical model of Quadratic Response Surface for Two Factors to determine the nitrogen fertilizer and irrigation levels that would maximize rice production and to analyze the effects of nitrogen fertilizer and irrigation on upland rice yield.  Analysis of variance (ANOVA) was used for the data collected form National Cereal Research Institute Badeggi, Niger State. The method of least square, R2 (coefficient of determination) and root mean square error (RMSE) was used to evaluate the rate of nitrogen (30, 60, 90, 120 kgNha-1) and (7, 14, 21days). The result showed that the models were adequate and significant at 5%. The results also indicated that application of 90-120kgNha-1and 7days interval of irrigation enhanced upland rice yield. It was also known that there was an increase in yield when there is frequent irrigation combined with application of nitrogen fertilizer (90-120kgNha-1) and computation of the data was adequate with R2 above 50% and root mean square error (RMSE) was very small.
Keywords: Irrigation; Least Square; Nitrogen fertilizer; Root Mean Square Error (RMSE); Significant at 5%